1988
DOI: 10.1097/00006842-198809000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Survival hazards analysis in first recurrent breast cancer patients: seven-year follow-up.

Abstract: The purpose of this study was to identify predictors of survival time in first recurrent breast cancer patients, including psychologic as well as biologic factors. Beginning in 1979, 36 women being treated at the National Institutes of Health for histologically proven recurrent disease were enrolled in this prospective study. At the time of data analysis, 24 had died from their malignancy. Through the use of a Cox proportional hazards model, four factors significantly entered the equation predicting survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 23 publications
0
42
0
2
Order By: Relevance
“…Some earlier studies suggested worse survival for breast cancer patients exposed to stress (Funch and Marshall, 1983;Levy et al, 1988). However, these associations have been weak because of methodological limitations, such as insufficient power and inadequate assessment of exposure were present in those studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some earlier studies suggested worse survival for breast cancer patients exposed to stress (Funch and Marshall, 1983;Levy et al, 1988). However, these associations have been weak because of methodological limitations, such as insufficient power and inadequate assessment of exposure were present in those studies.…”
Section: Discussionmentioning
confidence: 96%
“…Psychological stress may alter immune function that could influence tumour growth and metastasis (Cohen and Rabin, 1998;Kiecolt-Glaser and Glaser, 1999), but whether stress is associated with cancer survival is not clear (Funch and Marshall, 1983;Jamison et al, 1987;Levy et al, 1988;Tross et al, 1996;Levav et al, 2000). It has been proposed recently that stress may have no obvious effect on overall cancer survival, but could affect survival for specific cancers (Andersen et al, 1994;Kvikstad et al, 1995).…”
mentioning
confidence: 99%
“…A large body of research has been devoted to understand the role of psychosocial factors in determination of clinical outcomes of breast cancer [9]. Research evidences showed that psychological morbidity like helpless/hopelessness [10,11], hostility and guilt [12], chronic stress [13,14], extroversion and cognitive disturbance [15], lack of joy and negative mood [16], stressful life events [9,17,18], lack of perceived social support [19], obsessivecompulsive symptoms [20] adjustment problems [21], are experienced by one-third of women in the first two years after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores indicate greater levels of that affect state. The ABS has been utilized successfully to identify affect status in other studies of cancer patients (Derogatis et aL, 1979;Levy et al, 1988;Nelson et al, 1989). The Negative Affect Total (NAT) score was utilized in the present study analyses.…”
Section: Methodsmentioning
confidence: 99%